Economics of power systems : fundamentals for sustainable energy - Weber, Christoph; Möst, Dominik; Fichtner, Wolf (Springer texts in business and economics, 2022)
In order to manage the transition towards a sustainable future electricity system, an in-depth understanding of the key technological, economic, environmental and societal drivers for electricity markets is required. Suitable for advanced undergraduate and graduate students, this textbook provides an overview of these drivers and introduces readers to major economic models and empirical evidence for the study of electricity markets and systems.Readers will learn about electricity generation, demand, transport, and storage, as well as the fundamentals of grid and electricity markets in Europe. By introducing them to state-of-the-art models from operations research and economics, the book provides a solid basis for analytical insights and numerical modeling. Furthermore, the book discusses the policy instruments and design choices for electricity market regulation and sustainable power system development, as well as the current challenges for smart energy systems